2014
DOI: 10.1371/journal.pone.0103379
|View full text |Cite
|
Sign up to set email alerts
|

NAC Attenuates LPS-Induced Toxicity in Aspirin-Sensitized Mouse Macrophages via Suppression of Oxidative Stress and Mitochondrial Dysfunction

Abstract: Bacterial endotoxin lipopolysaccharide (LPS) induces the production of inflammatory cytokines and reactive oxygen species (ROS) under in vivo and in vitro conditions. Acetylsalicylic acid (ASA, aspirin) is a commonly used anti-inflammatory drug. Our aim was to study the effects of N-acetyl cysteine (NAC), an antioxidant precursor of GSH synthesis, on aspirin-sensitized macrophages treated with LPS. We investigated the effects of LPS alone and in conjunction with a sub-toxic concentration of ASA, on metabolic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 33 publications
2
48
1
Order By: Relevance
“…Finally, considering antiplatelet treatment, previous in vitro model studies demonstrated the implications of altered glutathione metabolism, ROS levels, and DNA damages in aspirin‐induced OS . In contrast with Raza et al , we did not find any difference in ROS, GSH, GSSG, and 8‐OHdG levels between patients treated with antiplatelet drugs and not treated patients.…”
Section: Discussioncontrasting
confidence: 97%
“…Finally, considering antiplatelet treatment, previous in vitro model studies demonstrated the implications of altered glutathione metabolism, ROS levels, and DNA damages in aspirin‐induced OS . In contrast with Raza et al , we did not find any difference in ROS, GSH, GSSG, and 8‐OHdG levels between patients treated with antiplatelet drugs and not treated patients.…”
Section: Discussioncontrasting
confidence: 97%
“…Aluminum caused extensive expression of astrocytes (gliosis) a condition seen in neurodegenerative conditions such as AD and PD (Raza et al 2014;Sharhripour et al, 2014) in Aluminum treated (Fig.5B) This is attributed to a sustained inflammatory response a crucial fact for the progression of neuron loss in AD (Wang et al 2015), this is term neuro-inflammation characterized by specialized response by activated glial cells (reactive gliosis) an oxidative stress mechanism (McGeer and McGeer 2008;Miller et al 2009). According to Deepmala et al (2015) and Batlle et al (2015) astrocytes are active during neuroinflammation to help neuron repair, support it during injury or toxic assault and restore cerebral homeostasis.…”
Section: Discussionmentioning
confidence: 95%
“…For this, cells were incubated with 5μM DCFDA for 30min at 37°C. Cells were washed twice with PBS, trypsinized, resuspended in 3ml PBS and fluorescence immediately analyzed by flow cytometry as described before [31].…”
Section: Measurement Of Reactive Oxygen Species (Ros) No and Lpomentioning
confidence: 99%
“…The total and oxidized glutathione are then measured from the standard curve and the GSH/GSSG ratios calculated. GSH-Px activity using cumene hydroperoxide [34] and GSH-reductase using oxidized glutathione (GSSG) [35] as substrates were measured by standard protocols as described before [31,33,36,37].…”
Section: Measurement Of Gsh Metabolismmentioning
confidence: 99%